If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + 2v = 0 Solving 5u + 2v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2v' to each side of the equation. 5u + 2v + -2v = 0 + -2v Combine like terms: 2v + -2v = 0 5u + 0 = 0 + -2v 5u = 0 + -2v Remove the zero: 5u = -2v Divide each side by '5'. u = -0.4v Simplifying u = -0.4v
| -9d^2=-405 | | 2xy-xz=4 | | 8*8=8 | | 11/4(5/3x-7/4) | | 8*8=111 | | 8*5=70 | | x/-3+12 | | 6u+v=18 | | (2+4)*5+10-18+7+5*(7+1)+4*0= | | 2t/3=4/9 | | 6c+3u=36 | | (3b-c-4)=2 | | 81x-8=1 | | 81x-=1 | | 4.6w+0.19=5539 | | 4x-y+8=2 | | 26=-3x+5 | | (4x-y+8)=2 | | 3x^4+8x^3-15x-40=0 | | 3(x+1)=y | | .018c=36 | | f(x)=(x^2+4x+4)-3 | | .4y=48 | | .06b=24 | | Y-x+1=1 | | .002t=6 | | .7a=490 | | -73=5n+78 | | (y-x+1)=1 | | sqrtx-2=x-8 | | 8x-7=-3(-12x-1)+4(-7x-3) | | 8x-7=-3(-12-1)+4(-7x-3) |